Sociological discourse in M.M. Khvostov's works - M.V. Novikov; T.B. Perfilova (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article analyzes the underlying aspects of the artistic heritage of M.M. Khvostov, an eminent professor at Imperial Kazan University. The focus is on the justification of the need for creating sociological history as a new type of explanatory history. The scholar’s coherent and consistent concept of sociological history was never introduced to the public, but its basics were laid and described in his publications and lecture courses. In this concept, history was qualified as an individualizing and idiographic study and sociology as a generalizing and nomothetic one. As a result of having stemmed from the belief in the unity of scientific methodology, M.M. Khvostov placed a greater emphasis on the overlapping of the subject fields and cognitive positions of these sociological branches rather than on their opposition. In order to overcome the opposition between the typological and concrete individual ways of comprehending historical reality, he proposed their theoretical and methodological synthesis on the principle of complementarity of tasks, research approaches, and methods. Therefore, the process of cognition was thought to involve studying unique facts, using the comparative historical method, as well as identifying common, similar, and typical features. The results obtained here are important for developing the theoretical and methodological foundations of historical science: M.M. Khvostov insisted that sociological history was destined to fill the existing abstract sociological schemes with reliable historical information, to contribute to the conceptualization of critically cited facts related to the multifaceted process of historical transformations of society.